Estudio sobre las condiciones que involucran la cirugía plástica estética a pacientes que acuden a la clínica quirúrgica ambulatoria Auhing, en el cantón de Quevedo, provincia de los ríos, año 2014 - Aguirre Flores, Diana Alejandra (2015)
This study runs directly to patients attending ambulatory surgical center Auhing, and the objective was to investigate conditions involving cosmetic plastic surgery because they see as a quick alternative to shape the body, however, it should emphasize that the most of the time one looks surgery because basically there is some uncertainty about self and in its pursuit of perfection, both modify any part of your body that end deforming. In the results it was observed that the reasons for surgery were that 43% were because they wanted to look younger, 30% by complexity, and 24% vanity. While 63% did not know the change that would occur with surgery but equally they were operated. 68% of the operated patients were influenced by the same parameters of beauty that society has implanted. The need to provide effective information from nurses to rub the psychosocial care of people who come to undergo cosmetic procedures because they are influenced by different rules or structures imposed on them by society is established. Keywords: Conditions Society, Plastic surgery, self-esteem, Addiction, Obsession.